Plant diversity in Mediterranean coastal dune systems subjected to anthropogenic disturbances - Younsi, Salah Eddine; Bouziane, Zahira (Biodiversity: Research and Conservation, 2023)
Mediterranean coastal dunes have an undeniable value in terms of floristic diversity as a result of their well-adapted plant species, such as psammophytes and halophytes. Unfortunately, these ecosystems are often disturbed by anthropogenic activities, such as the use of bathing settlements and trampling, the construction of paths or roads, and grazing by livestock. In this paper, these environmental factors were considered to determine their relative influences on several Algerian coastal dune systems undergoing ecological disturbance, by measuring in these systems various ecological gradients. Using ecological indices, multivariate analysis of data, and the analysis of variance, we compared the composition of the flora of 7 study sites that were subjected to various scales and types of disturbances. A total of 83 plant species were identified, reflecting the floristic richness of the sites. They seemed to be unevenly distributed and considerably modified according to environmental and human impact descriptors. The composition, abundance, and distribution of plant diversity are positively correlated with the height and width of the dunes. Regrettably, the floristic diversity of coastal dunes is more and more degraded by disturbance pressures (particularly grazing).